1991
DOI: 10.1073/pnas.88.9.3647
|View full text |Cite
|
Sign up to set email alerts
|

Improved serodiagnosis of hepatitis C virus infection with synthetic peptide antigen from capsid protein.

Abstract: Cloning and expression of hepatitis C virus have allowed the development of immunoassays to detect hepatitis C virus infection. However, currently available recombinant fusion protein C100-3 assays, based on a nonstructural protein of the virus, are limited in sensitivity, particularly for detecting acute infection. In this report seroconversion panels showed that an assay based on synthetic peptides, derived from immunodominant regions of both capsid and nonstructural proteins, accelerated hepatitis C virus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(59 citation statements)
references
References 24 publications
1
57
1
Order By: Relevance
“…Anti-HCV core antibody has been detected in the majority of patients with chronic hepatitis C (Chiba et al, 1991). HCV core protein contains immunodominant, highly conserved epitopes that elicit antibody production at an early stage of HCV infection (Harada et al, 1991 ;Hosein et al, 1991;Nasoff et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Anti-HCV core antibody has been detected in the majority of patients with chronic hepatitis C (Chiba et al, 1991). HCV core protein contains immunodominant, highly conserved epitopes that elicit antibody production at an early stage of HCV infection (Harada et al, 1991 ;Hosein et al, 1991;Nasoff et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The virus genome has been cloned and characterized as a 9.5-kb single stranded RNA (4,11). Several recombinant products of HCV cDNAs have been used as antigens to detect specific antibodies to the virus and have been useful in the diagnosis of HCV infection (3,10,13). We also isolated a cDNA clone derived from the plasma of a Japanese patient (15), and extended the cDNA to obtain the entire genome of Japanese HCV, HCV-N (9).…”
mentioning
confidence: 99%
“…Since it was found that 42% of these sera recognized both peptides, we believe that these antibodies might be responsable for some of the false positive results observed when using the O1 and 02 assays. An ELISA assay based on synthetic peptides has been recently published by Hosein et al (27). We have not had access to this assay and for this reason were unable to compare it with our own.…”
Section: Discussionmentioning
confidence: 99%